Vascularization of Engineered Spatially Patterned Myocardial Tissue Derived From Human Pluripotent Stem Cells in vivo - Wanjare, Maureen; Kawamura, Masashi; Hu, Caroline; Alcazar, Cynthia; Wang, Hanjay; Woo, Y. Joseph; Huang, Ngan F. (Frontiers in Bioengineering and Biotechnology, 2019)
Tissue engineering approaches to regenerate myocardial tissue after disease or injury is promising. Integration with the host vasculature is critical to the survival and therapeutic efficacy of engineered myocardial tissues. To create more physiologically oriented engineered myocardial tissue with organized cellular arrangements and endothelial interactions, randomly oriented or parallel-aligned microfibrous polycaprolactone scaffolds were seeded with human pluripotent stem cell-derived cardiomyocytes (iCMs) and/or endothelial cells (iECs). The resultant engineered myocardial tissues were assessed in a subcutaneous transplantation model and in a myocardial injury model to evaluate the effect of scaffold anisotropy and endothelial interactions on vascular integration of the engineered myocardial tissue. Here we demonstrated that engineered myocardial tissue composed of randomly oriented scaffolds seeded with iECs promoted the survival of iECs for up to 14 days. However, engineered myocardial tissue composed of aligned scaffolds preferentially guided the organization of host capillaries along the direction of the microfibers. In a myocardial injury model, epicardially transplanted engineered myocardial tissues composed of randomly oriented scaffolds seeded with iCMs augmented microvessel formation leading to a significantly higher arteriole density after 4 weeks, compared to engineered tissues derived from aligned scaffolds. These findings that the scaffold microtopography imparts differential effect on revascularization, in which randomly oriented scaffolds promote pro-survival and pro-angiogenic effects, and aligned scaffolds direct the formation of anisotropic vessels. These findings suggest a dominant role of scaffold topography over endothelial co-culture in modulating cellular survival, vascularization, and microvessel architecture.